Protective nutrition strategy in the acute phase of critical illness: why, what and how to protect - Wang, Youquan; Li, Yanhua; Li, Nan; Li, Yuting; Li, Hongxiang; Zhang, Dong (Frontiers in Nutrition, 2025)
Nutritional support is crucial for critically ill patients. Recent clinical studies suggest that both overfeeding during the acute phase of critical illness and overly conservative or delayed nutritional therapy can pose significant risks. Given substantial individual variability among critically ill patients, it is challenging to prescribe universally applicable and objective feeding strategies; Instead, we pointed out which nutritional interventions were harmful. We also summarized the reasons for protective nutrition, and elaborated the advantages of protective nutrition from three perspectives: gastrointestinal protection, nutritional protection and metabolic protection. In particular, it is emphasized that overfeeding will lead to metabolic disorders, such as mitochondrial dysfunction, autophagy inhibition, ketogenic inhibition, hyperglycemia, insulin resistance, etc. These detrimental processes can exacerbate one another, contributing to multiple organ dysfunction syndrome and poorer clinical outcomes. We also propose protective nutrition strategies comparable to lung protective ventilation strategies, which may benefit patients. Vigilant monitoring during nutritional implementation is also paramount, enhancing awareness of adverse events for early diagnosis and intervention to mitigate their harm.